Changes in cannabis, tobacco, and alcohol use among sexually active female adolescents and young adults over a twelve-year period ending in 2019. (October 2021) - Shyhalla, Kathleen; Smith, Danielle M.; Diaz, Angela; Nucci-Sack, Anne; Guillot, Mary; Hollman, Dominic; Goniewicz, Maciej L.; O'Connor, Richard J.; Shankar, Viswanathan; Burk, Robert D.; Schlecht, Nicolas F.
Highlights: Past 30-day cannabis use has increased 2 to 4-fold among inner-city female youth. Rates of past 30-day cannabis use were 2 to 10-times higher than reported nationally for women of the same age. Near daily cannabis use was significantly higher among women who engaged in same sex relationships. Past 30-day cannabis use was higher among women who also used tobacco, alcohol and other drugs. Abstract: Background: The United States has experienced an increasing divergence in cannabis, tobacco, and alcohol use among adolescents and young adults (AYA). We assessed the changes in cannabis, tobacco and alcohol use in an inner-city population of predominantly minority AYA females attending a large adolescent-specific health center in New York City. Methods: This was a longitudinal study of AYA women recruited and followed over a twelve-year period between 2007 and 2019. Lifetime and past 30-day use were assessed by self-administered questionnaire every six months. In addition, we assessed associations with race, ethnicity, sexual behaviors, receipt of social services, living situation at home (e.g., with or without parents), and use of other drugs. Results: Participants included 1549 AYA females aged 13–21 at baseline, 95% of whom were youth of color. Use of cannabis increased significantly over the twelve-year period, with frequent cannabis use (≥20 times in 30-days) increasing almost 18% per year (OR = 1.18; 95%CI:1.13–1.23). In contrast, past 30-day tobacco use declined over the same period (OR = 0.86; 95%CI:0.83–0.89). Past 30-day cannabis use was more likely among African Americans (OR = 1.33; 95%CI:1.08–1.63), women who had sex with both men and women compared to with men only (OR = 1.44; 95%CI:1.18–1.75), recent users of tobacco (OR = 2.20; 95%CI:1.92–2.52) and alcohol (OR = 2.84; 95%CI:2.52–3.20), and ever users of other drugs (OR = 1.69; 95%CI:1.44–1.99), independent of age, time and living situation. Conclusions: Increasing rates of cannabis use and the association with concurrent tobacco and alcohol use in AYA females underscore the need to screen for unhealthy cannabis use, in addition to tobacco and alcohol, especially among inner-city AYA.